Analisis Perbandingan Volume Perdagangan Saham, Abnormal Return dan Frekuensi Saham Perusahaan Sektor Energi Yang Terdaftar di Bursa Efek Indonesia Sebelum dan Sesudah Pelarangan Ekspor Batubara untuk Ketahanan Energi Dalam Negeri 2022 - Habibillah, R Apriyanto; Nugroho, Prasetyo (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
This study aims to find out and compare the trading volume activity, abnormal return  and frequency of trading shares of energy companies before and after the announcement of the ban on export coal  for Domestic Market Obligation in Indonesia.The population in this study are companies that are included in the Energy Sector listed at IDX. The samples in this study used purposive sampling, where only 17 companies met the criteria. In this  study, the data used is 14 days before and after the announcement of the ban on export coal  for Domestic Market Obligation in Indonesia. The hypothesis test used is Wilcoxon Signed Rank Test. The result showed that: 1) there is a significant  differences in the trading volume and frequency trading share of sample  companies before and after the ban on export for Domestic Market Obligation, 2) there is no significant difference in the abnormal return of sample companies before and after the ban on export for Domestic Market Obligation.